2022
DOI: 10.1177/17511437221091051
|View full text |Cite
|
Sign up to set email alerts
|

Coercion in intensive care, an insufficiently explored issue—a scoping review of qualitative narratives of patient’s experiences

Abstract: Purpose The use of coercion, in a clinical context as imposing a measure against a patient’s opposition or declared will, can occur in various forms in intensive care units (ICU). One prime example of a formal coercive measure in the ICU is the use of restraints, which are applied for patients’ own safety. Through a database search, we sought to evaluate patient experiences related to coercive measures. Results For this scoping review, clinical databases were searched for qualitative studies. A total of nine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(111 reference statements)
0
0
0
Order By: Relevance
“…6 13 Patients have described long-lasting and vivid memories of restraint in somatic care, as well as being negatively affected by their experiences. 14 Several studies have also reported on cases of death caused by physical restraint in somatic care. 15 16 The studies from somatic care settings are buttressed by an extensive literature reporting on physical and psychological harm caused by restraint in psychiatric care.…”
Section: Introductionmentioning
confidence: 99%
“…6 13 Patients have described long-lasting and vivid memories of restraint in somatic care, as well as being negatively affected by their experiences. 14 Several studies have also reported on cases of death caused by physical restraint in somatic care. 15 16 The studies from somatic care settings are buttressed by an extensive literature reporting on physical and psychological harm caused by restraint in psychiatric care.…”
Section: Introductionmentioning
confidence: 99%